Learning Disabilities in Neurofibromatosis Type 1 - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The frequency of specific leaning disabilities (SLD) in neurofibromatosis type 1 (NF1) was determined in a cohort of 81 patients (43 males, 38 females; mean age 11 years 6 months; age range 8-16) followed at Children's Hospital, Westmead, NSW, Australia.